Focal adhesion mediated regulation of pluripotency : The role of focal adhesions and contractile forces in human pluripotent stem cells - Stubb, Aki (fi=Turun yliopisto|en=University of Turku|, 2019)
Human pluripotent stem cells (hPSCs) hold great promise for future medicine. They can differentiate to all adult cell types and self-replicate virtually endlessly. These features would make hPSCs a valuable tool for applications of regenerative medicine. Pluripotency is controlled by extracellular cues which establish the correct culture conditions. Appropriate growth factors and extracellular matrix (ECM) composition must be provided for maintenance of viability, pluripotency and self-renewal in vitro. However, the stem cell field has overlooked many of the basic cell biological phenomena that could affect the regulation of pluripotency. Focal adhesions (FAs) connect the ECM via integrin receptors to the cellular cytoskeleton. They are dynamic protein complexes responsible for broadcasting the information of composition and mechanical properties of the ECM to biochemical intracellular signalling cascades. Furthermore, they provide the physical anchoring points needed for cell adherence and movement. FAs have not been studied in the context of human pluripotency before. In this thesis, I utilise high-resolution microscopy to describe for the first time the characteristics of FAs in hPSCs. We show that hPSCs have large cornerstone FAs connected via contractile actin stress fibres at colony periphery. We provide evidence that structures at the colony edge create traction forces needed for compaction of the cells. Also, we show that FAs function as signalling platforms. We employ 3D superresolution microscopy and unveil unique ultrastructural features of large FAs and show that perturbation of the structure accelerates hPSC differentiation. Finally, we introduce a versatile, easy access method for implementation of fluctuation based super-resolution microscopy to measure cellular forces in nanoscale. In summary, this thesis provides in detail characterisation of cornerstone FAs in hPSCs and highlights their role for morphological features of the colonies and pluripotency. In addition, it provides a new method for studying cellular forces exerted by the FAs.